Outcomes of operative and nonoperative management of myotendinous Achilles tendon ruptures: a systematic review - Darius L. Lameire; Luca Ramelli; Mansur Halai; David Wasserstein; Sam Si-Hyeong Park (BMC Musculoskeletal Disorders)
Abstract Background Achilles tendon ruptures are the most common lower extremity tendinous rupture. While there has been extensive research into the management of mid-substance Achilles tendon ruptures, there is a paucity of literature on the management of myotendinous Achilles tendon ruptures. Methods The aim of this systematic review is to compile all available literature on the treatment of myotendinous Achilles tendon tears. A systematic search of Web of Science, Embase, and Medline databases was performed for all studies published from database inception to April 13, 2024. All publications addressing the treatment of myotendinous Achilles ruptures of all levels of evidence were included. The PRISMA Checklist guided the reporting and data abstraction. Descriptive statistics are presented. Results A total of five studies with 70 patients were included for analysis. Sixty-seven patients underwent non-operative management with an average age ranging from 40.8 to 51.0 years. Three patients underwent operative management with ages of 16, 36, and 39. The majority of patients tore their Achilles tendon during sports. For nonoperatively treated patients, one group underwent immobilization for a total of 6 weeks and one study treated patients with functional rehabilitation. All patients were able to perform a single heel-raise, had good reported strength, and returned to work or sport. Nonoperative patients reported statistically significant improvements in subjective outcomes and high rates of satisfaction. Conclusion Both nonoperative and operative management of myotendinous Achilles tendon ruptures demonstrated good outcomes after injury, although there is a limited amount of literature on this topic. Given that nonoperative treatment appears to yield good strength and return to activity, it may be preferred for the majority of patients. Operative management may be indicated in high level athletes. Imaging to determine the exact location of injury, quality of remaining tendon, and gap distance may further aid when considering treatment options. Higher level evidence studies are required to determine the optimal treatment of myotendinous Achilles tendon ruptures. Level of evidence IV; Systematic review of Level IV-V studies.